Dinheiro direto na escola, gestão democrática e público não-estatal: uma avaliação do Programa de Manutenção e Desenvolvimento do Ensino de Fortaleza - Campelo, João Inácio (2011)
This evaluative study presents the results of the work entitled "Money in the school direct, democratic management and non-state public: an evaluation of the Programme for the Development of Education - PMDE in Fortaleza," whose main objective was to evaluate the Program Development and Maintenance Education (PMDE) in the context of the Brazilian educational reform, as well as its implications for the management of public schools. The defense of public policy for the creation of the program lies in categories such as decentralization, transparency, participation, autonomy and democratic management. Our overall objective therefore was to analyze the deployment and implementation of PMDE while thread for possible developments in the process of democratic management of education, autonomy of schools and in the implications for the organization and operation of public school in Fortaleza, of the formation School Council (EC) in Executing Units (UEX) as private entities linked to the nonprofit school. The design methodology that guided the development of the research took into account the peculiarities of the importance of schools in the sample, the power relations manifest and the specific embodiment of the present government policy. Given this methodological demand, the study was conducted in two school units, with one belonging to the Regional Secretariat (SER) and another being I VI. In conclusion, it is important that the PMDE has many positive aspects, including the real possibility of collective participation of the various segments that make up the EC and the financial autonomy of the school, which is a historic battle flag of the educators. However, continuing reflection in the sense that the decentralization of education financing municipal public money split into direct programs in school as PMDE, can not be opened to door to privatization of education. The struggle of civil society must continue to ensure the public school the character state in funding, the community character as to its management, and public character as to its destination.